Herbal Agents Having Abortive Activity - Saha, Anumita; Chatterjee, Aishi; Singh, Shristi; Ghosh, Jaya; Majumdar, Mrityunjoy; Roy, Sourav; Roy, Prodip (Journal for Research in Applied Sciences and Biotechnology, 2022)
The goal of our study is to increase public awareness of natural contraceptives and their powerful advantages over surgical abortion in order to provide people with an alternative method of ending an unwanted or unplanned pregnancy rather than the dreaded surgical procedure. Since ancient times, traditional remedies have been used all across the world to control fertility. Still, the tribal community mostly relies on these herbs for contraception and to cause abortions. The belief in therapeutic approaches has not been diminished despite the tremendous advancement of allopathic treatment because of its negative side effects. Plants and herbs have been used to induce abortions, although there is very little published information on the most regularly used ones. The grail of this paper is to detail the herbal products used to cause abortion.